2020
DOI: 10.4067/s0718-381x2020000200198
|View full text |Cite
|
Sign up to set email alerts
|

Análisis Cinemático de la Masticación de una Granola Prototipo en Contraste con la Masticación de Maní

Abstract: RESUMEN: La masticación se ha estudiado desde diferentes puntos de vista, utilizando alimentos de prueba naturales y artificiales. La evidencia es escasa cuando se analizan alimentos a base de cereales, que van desde cereales para el desayuno hasta barras de granola. El investigar este tipo de alimentos, se vuelve importante para entender el comportamiento de la masticación frente a alimentos con diferentes composiciones y texturas, y como estas características pueden influir en el proceso masticatorio. Se ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…12, 13 Different test foods have been used to study mastication, from natural foods with variable textures and compositions -e.g., peanut, banana, carrot, prototype granola. 14, 15 -to synthetic materials with standard characteristics, such as chewing gum and bag-ged silicone like Optosil. 6,16, 17 Which have been used for masticatory efficiency and performance studies, as well as for the kinematic analysis of the mastication.…”
Section: Palabras Clavementioning
confidence: 99%
“…12, 13 Different test foods have been used to study mastication, from natural foods with variable textures and compositions -e.g., peanut, banana, carrot, prototype granola. 14, 15 -to synthetic materials with standard characteristics, such as chewing gum and bag-ged silicone like Optosil. 6,16, 17 Which have been used for masticatory efficiency and performance studies, as well as for the kinematic analysis of the mastication.…”
Section: Palabras Clavementioning
confidence: 99%
“…Another food that has been analyzed and its results compared with peanut is cereal-based granola. With a size similar to the peanut, it has been reported that subjects with removable protheses execute wider masticatory movements when chewing granola, and higher values are generally reported for variables such as frequency, speed and area of masticatory cycles compared to the peanut, which is recognized as a food that stimulates chewing and therefore is highly recommended from a mechanical point of view for those subjects who have dental prostheses and who have seen their movements reduced as they lose teeth (Farfán et al, 2020).…”
Section: Type Of Foodmentioning
confidence: 99%